Lukion vieraiden kielten opettajien käytänteitä ja käsityksiä eriyttävästä arvioinnista (Foreign language teachers´ practices and perceptions of differentiated assessment in upper secondary schools) - Roiha Anssi; Nieminen Juuso; Mäntylä Katja (Suomen Soveltavan Kielitieteen Yhdistys AFinLA ry, 2023)
This study explores the perceptions and practices of upper secondary school language teachers on differentiated assessment. The data were collected through a closed and open-ended questionnaire (n=48) and individual interviews with four teachers. The results show that the teachers used a variety of assessment methods, with a predominant emphasis on formative assessment. Although the teachers mentioned many differentiated assessment methods, they did not generally differentiate their assessments to a large extent. The teachers also focused mostly on low-achieving students and neglected adversely gifted students. The teachers seemed to follow the practice of having all students demonstrate their learning in the same way and at the same time. Class size was seen as the main barrier to more thorough differentiation. The results of this study suggest that differentiation should be better integrated into assessment and that both pre- and in-service teachers would benefit from training focusing on differentiated assessment.
Kielenoppimista tukeva arviointi (Assessment for supporting language learning)